Styles of Representation and Voters' Evaluations of Democratic Performance: Parties and Party Voters. Issue 2 (2nd July 2016) - Önnudóttir, Eva H.
Abstract : This paper combines the nature and outcome of representation by analysing how different styles of representation emphasised within parties explain party voters' evaluations of the performance of liberal democracy in their country, using for parties the Comparative Candidates Survey and for voters the European Social Survey 2012. Styles of representation are defined at the party level as the proportions of representatives within parties who are partisans, delegates or trustees. The results show that the more the trustee style is emphasised within parties, the more positively the performance of liberal democracy is evaluated. The relation for the delegate style is inverse; the more that style is emphasised, the more negatively democratic performance is rated, while the effect for the partisan style is negligible. It is argued that trustee parties are those who gain from the current political system, and are able to mobilise voters who evaluate liberal democracy positively, as opposed to voters of delegate parties which are less satisfied and evaluate democratic performance more negatively.